Fishery and bionomics of the little tuna, Euthynnus affinis (Cantor, 1849) exploited from Indian waters - Prathibha, Rohit; Chellappan, Anulekshmi; Abdusssamad, E. M.; Joshi, K. K.; Said Koya, K. P.; Sivadas, M.; Ghosh, Shubhadeep; Margaret Muthu Rathinam, A.; Kemparaju, S.; Dhokia, H. K.; Prakasan, D.; Beni, N. (Indian Journal of Fisheries, 2012)
Euthynnus affinis, with an average annual landing of 40,757 t during 2006-2010 formed the bulk (65.1%) of the total coastal tuna catch of the country. The fishery, biology, growth and stock structure of E. affinis was studied in detail. Hooks and lines, gillnets and purseseines were the major gears exploiting the fish. Fishery was sustained mainly by 1 - 2 year old fishes (34 to 50 cm). Size at first maturity was estimated at 37.7 cm and fecundity was 3,08,150 eggs. Spawning was observed round the year with peaks during July-August and November-January. E. affinis was found to be a nonselective generalist feeder foraging on fishes, crustaceans and molluscs. The lengthâ€“weight is given by the relationship 0.0254 L2.889 with no significant difference between males and females. Age and growth were estimated using length based methods. The von Bertalanffy growth parameters estimated were Lâˆž = 81.92 cm, annual K= 0.56 and t0 = -0.0317. Mortality estimates were M= 0.93 and Z = 1.68 and F= 0.75 with the exploitation rate E=0.45. The maximum sustainable yield estimated was higher than the average annual catch indicating scope for further exploitation.